2021
DOI: 10.1101/2021.03.23.436714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Euchromatin factors HULC and Set1C affect heterochromatin organization for mating-type switching in fission yeastSchizosaccharomyces pombe

Abstract: Mating-type switching (MTS) in fission yeast Schizosaccharomyces pombe is a highly regulated gene conversion event. In the process, heterochromatic donors of genetic information are selected based on the P or M cell type and on the use of two recombination enhancers, SRE2 promoting use of mat2-P and SRE3 promoting use of mat3-M. Recently, we found that the histone H3K4 methyltransferase complex Set1C participates in donor selection, raising the question of how a complex best known for its effects in euchromati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 74 publications
(193 reference statements)
0
6
0
Order By: Relevance
“…In addition, the AT-hook motifs might both foster interaction of Swi2 directly with SRE2 , and act indirectly through SRE3 to increase Swi2 occupancy in the whole region. In M cells, we suggest that Set1C also works at SRE3 to modulate chromatin conformation (Esquivel-Chavez et al ., 2022; Maki et al ., 2018). While further work is necessary to elucidate the molecular mechanisms underlying Swi2 localization, our in vitro investigations provide new clues for how Swi2 would stimulate recombination when localized at a donor locus and for its cell-type specific properties.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In addition, the AT-hook motifs might both foster interaction of Swi2 directly with SRE2 , and act indirectly through SRE3 to increase Swi2 occupancy in the whole region. In M cells, we suggest that Set1C also works at SRE3 to modulate chromatin conformation (Esquivel-Chavez et al ., 2022; Maki et al ., 2018). While further work is necessary to elucidate the molecular mechanisms underlying Swi2 localization, our in vitro investigations provide new clues for how Swi2 would stimulate recombination when localized at a donor locus and for its cell-type specific properties.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, we reported that two euchromatin factors, Set1C and HULC, inhibit the choice of mat3-M as a donor in M cells, probably by affecting chromatin structure at SRE3 (Esquivel-Chavez et al ., 2022; Maki et al ., 2018). We analyzed the possible involvement of these euchromatin factors in the function of Swi2 (Figure 6C and Supplementary Figure S3D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations